Electrochemical determination of oxalic acid using palladium nanoparticle-loaded carbon nanofiber modified electrode - Liu, Yang; Huang, J.; Wang, D.; Hou, H.; You, T. (R S C Publications, 2010)
We have developed a novel electrochemical oxalic acid (OA) sensor based on the palladium nanoparticle-loaded carbon nanofiber (Pd/CNF) composites. These composites with large amounts of spherical nanoparticles well dispersed on the carbon nanofibers (CNF) were produced by combination of electrospinning technique with thermal treatment method. When applied to oxidation of OA, the Pd/CNF modified carbon paste electrode (Pd/CNF-CPE) exhibited high electrocatalytic performances with fast voltammetric responses and notably decreased overpotential compared to the bare and even the CNF modified CPE. A detection limit of 0.2 mM with linear ranges of 0.2–13 mM and 13–45 mM can be obtained at the Pd/CNF-CPE. Based on its high sensitivity and good selectivity, the proposed method was applied to determination of OA in spinach, and the satisfactory results confirmed the applicability of this sensor in practical analysis.